Análise ecotoxicológica de sedimento do estuário da Baía de Vitória (ES) com diferentes granulometrias - Santos, Andreia Carvalho dos (2011)
The Bay of Vitória (ES, Brazil) comprises an important estuarine system and one of the most significant port complexes in Brazil. Port activities along with intense urbanization are responsible for environmental damages in the area, including constant dredging and landfills. The main source of contamination in the area is sewage dumping from continental drainage. This study characterizes sediments from some points of the bay according to location, granulometry, and toxicity in order to contribute to analyzing the laws regulating sediment monitoring during dredging events. During remobilization, sediment is resuspended with contaminants to the water column, which can cause impacts on both dredged and disposal areas. Sediment toxicity with different grain sizes was assessed through acute ecotoxicological testing with bacterium Vibrio fischeri, and chronic ecotoxicological testing with microalgae Skeletonema costatum. The physical-chemical analyses and tests with Skeletonema costatum were performed through elutriation, and the tests with Vibrio fischeri used interstitial water. Nine (9) different sediment collection points, with varied sand and mud contents, were selected. The results obtained from ecotoxicological testing showed correspondence between sediment toxicity and proximity to contamination sources. However, this was not found for the relation between mud content and contamination. Some collection points presented toxicity despite the fact that mud content was low (≤ 10%). This contributes to the discussion about the guidelines and proceedings in the CONAMA (Brazilian Council for the Environment) Resolution 344/04. We verified that sediments of an estuary or bay cannot be deprived from monitoring based only on grading regardless of the amount being dredged without taking the contamination and proximity to contamination sources into account